Combustion characteristics and thermal properties of high-density polyethylene/ethylene vinyl-acetate copolymer blends containing magnesium hydroxide. (October 2017) - Ma, Yonghong; Chen, Man; Liu, Nian; Dang, Pengyu; Xu, Yang; Chen, Xiaolang; Wang, Zhao; He, Jiang
Magnesium hydroxide (MH) was added into high-density polyethylene (HDPE)/ethylene vinyl-acetate (EVA) copolymer blends with various MH contents (30–60 wt%) to improve the flame retardancy of HDPE/EVA blends. The flammability, morphology of charred residues, thermal stability, crystallization, and mechanical properties of HDPE/EVA/MH composites were investigated by UL-94 test, limiting oxygen index (LOI), cone calorimeter test (CCT), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and tensile test. The data obtained from LOI, UL-94 test, and CCT revealed that the addition of MH provided improvements in flame retardancy by increasing the LOI values, UL-94 rating, and reducing heat release, carbon monoxide and carbon dioxide emissions along with delayed ignition with increasing the content of MH. The UL-94 V-0 rating and high LOI value were achieved with the incorporation of MH at a loading level higher than 50 wt% in HDPE/EVA blends, which suggested that the formation of intact, consolidated, and thick residue structures on the surfaces of MH-filled composites prevented the underlying polymer materials from burning. DSC results showed that the crystallinity of HDPE/EVA blends increased with increasing the content of MH, resulting in the enhancement of the strength of HDPE/EVA/MH composites. The thermal stability of HDPE/EVA blends decreased due to the addition of MH.